CREB3 Transactivates lncRNA ZFAS1 to Promote Papillary Thyroid Carcinoma Metastasis by Modulating miR-373-3p/MMP3 Regulatory Axis - Gang Wang; Yuan Le; Liping Wei; Lian Cheng (International Journal of Endocrinology)
The incidence rate of thyroid carcinoma ranks ninth among human malignancies, and it accounts for the most frequent malignancy in endocrine-related tumors. This study aimed to investigate the role of long noncoding RNA (lncRNA) ZFAS1 in the metastasis of papillary thyroid carcinoma (PTC) and the potential molecular mechanisms. Both ZFAS1 and MMP3 were highly expressed in thyroid carcinoma and PTC cell, as measured by the q-PCR and TCGA database. In addition, ZFAS1 induced TPC-1 metastasis through inducing the epithelial–mesenchymal transition (EMT) process. Besides, ZFAS1 knockdown by siRNA induced miR-373-3p expression and reduced MMP3 expression, as quantified by q-PCR and Western blotting. According to the luciferase assay, both ZFAS1 and MMP3 were classified as the direct targets of miR-373-3p. However, MMP3 itself did not affect ZFAS1. Using the online prediction tool, CREB3 was predicted as the transcription factor (TF) of ZFAS1 that contained two binding sites on its promoter region, and CREB3 was positively correlated with ZFAS1 in thyroid carcinoma cohorts. Results from the dual-luciferase assay and ChIP-qPCR indicated that both the two binding sites were essential for the transcription of ZFAS1. In conclusion, CREB3 activated lncRNA ZFAS1 at the transcriptional level to promote PTC metastasis by modulating miR-373-3p/MMP3.